Economics of culture and food in evolving agri-food systems and rural areas - Severino Romano; Francesco Vanni; Davide Viaggi (Bio-based and Applied Economics (BAE), 2020)
The role of culture in connection with the development of food and bioeconomy issues has gained growing importance in recent years. In this editorial we provide background information on the three key topics addressed by the papers published in this special issue: cultural ecosystem services, cultural issues in the organisation of food chains, culture and food characteristics. In a way, the common denominator of these papers is the link between culture, food and territory, taken from different angles. More research and methodological advances are needed for a better consideration of culture in economic research accounting for the current needs of more systemic and holistic vision of the topic.
Keywords: O13; Q13; Q18; Q57; 330; Culture; agricultural economics; food economics; cultural ecosystem services; food chains; food characteristics